Optimizing Sustainability: Pemula Peternak Puyuh dan Inovasi Kompos Limbah Organik sebagai Pemacu Pertanian Berkelanjutan - Wahidin; Roni; Anisa Sains Kharisma (Universitas Veteran Bangun Nusantara, 2024)
The involvement of young quail farmers is essential for understanding their role in adopting practices such as composting quail manure. The participants in this Community Service activity are the younger generation, specifically the children of quail farmers in Grinting Village. This approach aims to cultivate environmentally conscious and committed young quail farmers dedicated to sustainable farming practices. The Community Service method is divided into three components: (1) Providing Insight on the Importance of Quail Livestock Waste Management for Young Beginner Farmers, (2) Composting Practice with Quail Manure, and (3) Completing the Compost Understanding Questionnaire. During this Community Service activity, straightforward yet easily comprehensible discussion material was presented on the preparation of young quail farmers. Their practical involvement in quail farming needs enhancement to foster a more comprehensive understanding. The primary focus is on establishing a fundamental understanding of quail farming as an economic potential, with a particular emphasis on ethical responsibility regarding livestock waste management, encompassing both manure and feed residues. The severe consequences of ineffective waste management are elucidated, including the impact of pollution on water and air, as well as associated health risks and economic losses. Awareness of the importance of adhering to environmental regulations is emphasized for the sustainability and safety of livestock. Technical solutions, such as optimal cage design and composting, are recommended to achieve a clean environment and enhance livestock productivity. Active participation of prospective farmers in waste management practices and collaboration with fellow farmers are strongly encouraged. Additional resources, in the form of guides and visual materials, are provided to support the implementation of these concepts